Dental hygiene registration: development, and reliability and validity testing of an assessment scale designed for nurses in institutions. Issue 13 (18th April 2017) - Fjeld, Katrine Gahre; Eide, Hilde; Mowe, Morten; Hove, Lene Hystad; Willumsen, Tiril
Abstract : Aims and objectives: To develop and test the dental hygiene registration, a dental hygiene assessment scale for nurses working in institutions. Background: Removal of dental plaque is a key factor in preventing oral health‐related diseases. A simple, but reliable dental hygiene assessment scale that enables nurses to monitor residents' dental hygiene on a daily basis, will improve monitoring oral hygiene status and quality of dental health care. Design: Descriptive study on the development and evaluation of a dental hygiene registration instrument. Methods: The dental hygiene registration was developed and tested over several stages during the period of 2011–2014. Dental hygiene registration consists of a five‐point plaque score scale. The score indicates whether measures are needed. A reference group comprising both medical and dental personnel designed dental hygiene registration. Dental plaque was used as a measure of dental hygiene. A pictorial series of teeth with varying amounts of plaque was used to achieve intra‐examiner agreement. Dental hygiene registration assessments were scored 50 times to assess interexaminer reliability between one dental hygienist and one clinical nurse. Dental hygiene registration was validated against the plaque index score of the Simplified Oral Hygiene Index. The Regional Ethics Committee approved the study (2011/915). Results: Estimates for intra‐examiner agreement on plaque score were good for the dental hygienist (κ = 0·7) and very good for the clinical nurse (κ = 0·8). Estimates for interexaminer reliability for dental hygiene registration between the dental hygienist and the clinical nurse were moderate (κ = 0·4). dental hygiene registration corresponded significantly with Simplified Oral Hygiene Index (Spearman's correlation coefficient = 0·8, p < 0·001) indicating good validity. Conclusion: The developed dental hygiene registration appears to be reliable and valid. Relevance to clinical practice: Dental hygiene registration may contribute to the provision of daily oral care. Dental hygiene registration enables nurses to evaluate their own effort when assisting in dental hygiene and to register whether further effort is needed.